Media Portrayal and Perpetuation of Rape Myths: A Systemic Functional Linguistics Analysis of Noor Mukaddam’s Case in Pakistani Print Media - Naveed Akram; Musarat Yasmin (University of Chitral Journal of Linguistics and Literature, 2024)
Sexual violence against women has been the focus of research across the globe for decades. Intimate partner violence is one special kind that carries patriarchal socio-cultural beliefs with it governing and perpetuating such form(s) of sexual violence. Women become the victims of rape, torture, mental trauma and even murder. This paper studies sexual violence against women with special reference to Noor Mukaddam’s case and its portrayal in Pakistani print media. Noor was the daughter of a Pakistani ex-diplomat whom Zahir Jaffar, her friend, brutally tortured and beheaded afterwards on 20th July 2021. ‘Transitivity analysis’ and ‘Appraisal’ features of the selected news reports with the help of Systemic Functional Linguistics (SFL) reveal that the print media sometimes misreport the news of sexual violence that may easily go in the favor of the involved perpetrators. Such misreporting may discursively perpetuate rape myths and wrong beliefs having no sound logic. Objective news reporting may help focus on the ‘real issue’ without decentralizing the attention from the crime to the sensational elements.